2021
DOI: 10.1002/bies.202100087
|View full text |Cite
|
Sign up to set email alerts
|

Personalized health and the coronavirus vaccines—Do individual genetics matter?

Abstract: Vaccines represent preventative interventions amenable to immunogenetic prediction of how human variability will influence their safety and efficacy. The genetic polymorphism among individuals within any population can render possible that the immunity elicited by a vaccine is variable in length and strength. The same immune challenge (virus and/or vaccine) could provoke partial, complete or even failed protection for some individuals treated under the same conditions. We review genetic variants and mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Though recent work has demonstrated that higher binding antibodies correlate to higher neutralizing antibodies ( 13 ), expansive, multi-center longitudinal studies profiling the cellular and humoral response are needed. Comprehensive future work would benefit from characterizing immunogenetic determinants for SARS-CoV-2 vaccine effectiveness ( 44 , 45 ) via a so-called “Adversomics” approach ( 46 ) and should include profiling of quantitative binding antibodies, neutralizing and non-neutralizing antibodies, memory B-cells, and T-cell responses, as immune protection appears to be contingent on all three tiers of the immune response ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though recent work has demonstrated that higher binding antibodies correlate to higher neutralizing antibodies ( 13 ), expansive, multi-center longitudinal studies profiling the cellular and humoral response are needed. Comprehensive future work would benefit from characterizing immunogenetic determinants for SARS-CoV-2 vaccine effectiveness ( 44 , 45 ) via a so-called “Adversomics” approach ( 46 ) and should include profiling of quantitative binding antibodies, neutralizing and non-neutralizing antibodies, memory B-cells, and T-cell responses, as immune protection appears to be contingent on all three tiers of the immune response ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the expression of ACE2 along the differentiation of human monocytes to mature DCs and inter-donor were found. DCs interaction with SARS-CoV-2 S protein is extremely relevant considering the current wide use of S protein-based vaccination protocols [ 19 ]. DCs maturation upon S protein binding is expected to be a key step to induce long-lasting immunity against this virus.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and heterogeneity of the immune response to vaccines is still a potential issue in providing vaccines to the public ( Poland et al, 2007 ) . Public health vaccination policies can usually take the individual characteristics of age and disease comorbidity into account but rarely consider the genetic background ( Valdés-Fernández et al, 2021 ). The advent of high-throughput sequencing technologies has allowed obtaining individual genomic information fast and accurately ( Poland et al, 2007 ; Seib et al, 2009 ).…”
Section: Personalized Vaccinesmentioning
confidence: 99%